Lietuvių-latvių etimologijos - Karaliūnas, Simas (Baltistica, 1970)
LITHUANIAN-LATVIAN ETYMOLOGIESLatv. buôzt “bristle” seems to be derived from the noun Latv. buõze “stiek, club with a thick end”. Latv. buõze and Lith. búožė “knob, stick, club with a thick end; flail etc.” are apparently connected with Latv. bâzt “put, set, stick, fix”, Lith. božóti “slice”, Latv. bêzt2 “shoot, scratch, shuffle” (concerning their meaning cf. Lith. bèsti “stick” and Latv. best “dig, spade”). Some parallels, cf. Lith. žiáunos “branchia, gills”, Latv. žaũnas “gills; jaw; mouth” and OCS žują “I chew, masticate”; Goth, munþs, OE mūth “mouth” and Lat. mando “I chew, masticate, eat, bite”, show that Lith. burnà “mouth” (Latv. pur̂ns “muzzle; snout” is supposed to be from *burn-) goes back to the Baltic root *br̥-H- “rub, grate, grind; chew, masticate” attested in Latv. bur̂nît “ąsqueeze, pinch, crumple, rub”, bur̂zît, bur̂zêt “rub, crumble, crease”, Lith. bir̃žti “to make a sign in a soil with the foot so that a sower could see how wide to sow”, Latv. bêrzt “rub, scrub, wash, chafe”. Lith. čáižyti and čiáužyti “lash, switch, whip” are derivatives of Lith. číežti “lash, whip”, čéižti “to litter” and respectively čiaũžti “slide, glide”. Latv. drīzs “fast, quick, swift; soon” can be identified with Lith. drỹžti “tear”, dríežti “tear”. For their semantical connection some evidence is furnished by Lith. dréngti “wear, tear; rub, grind off, file off; hurry, make haste”; Lith. griẽti “snatch, seize, grasp, grab, tear; skim the milk, take the cream off; drive etc.” Lith. greĩtas “quick, rapid, fast; prompt, speedy; near”, Latv. griets “quick, fast, swift; rapid, prompt”; OHG rase, OE rash “quick, fast, rapid”: Ir. rethim “Irun.” Lith. gubyti “toss, beat, flog” wich corresponds to Latv. gubît “rob, steal, plunder etc.” provides an internal connection with Lith. gùbti “become hollow, sunken”, gaũbti “bend, turn outwards; rob, plunder”. Lith. kam̃pas “handle, grip; shaft-bow”, Latv. kam̃ps “a bow of a basket” are most likely derived from the verb Lith. kam̃pti, Latv. kàmpt “seize, catch, grasp” (cf. Lat. capulus and capio and others). Lith. šẽškas, Latv. sȩsks “fitchew” are considered to be derivations with suffix -(s)k- from the verbal root šeš- which lurks in Lith. šešti “to be angry, to cavil, to carp”, šešus “angry, captious, fault-finding, carping”, šãšas “scab; abscess, boil, sore”, Latv. sass “scab; itch etc.”. In view of OCS gnĕvъ “anger, malice, wrath”, Russ Ch gnĕvъ “rotten stuff”, OCS gniti “rot, putrefy” and other evidence in the Indo-European languages it is possible to reconstruct for the root šeš- its primary meaning “to rot, to putrefy, to become dirty, putrid, to stink”. To denominate a fitchew after its stench is a well-known fenomenon in the Indo-European languages (cf. e. g. the etymologies of ORuss dъchоrъ, OHG wisula, OFr voison and to some extent E fitchew). The same root šeš- “to rot, to putrefy, to become dirty, putrid, to stink” could be reflected in such Lithuanian and Latvian river names as Šešùpė, Šešuvà, Sesava and others.